Comparison of diagnostic efficacy of 18F-FDG PET/CT and 68Ga-DOTANOC PET/CT in ectopic adrenocorticotropic hormone syndrome - Zhang, Bing; He, Qiao; Long, Yali; Zhang, Yuying; Wang, Xiaoyan; Chen, Zhifeng; Liu, Jianbo; Zhang, Xiangsong (Frontiers in Endocrinology, 2022)
Purpose Fluorine-18 (18F)-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) and gallium-68 (68Ga)-somatostatin analog (SSA) PET/CT imaging have been increasingly used in ectopic adrenocorticotropic hormone syndrome (EAS); however, the diagnostic efficacies of these two methods in patients with EAS remain unclear. Our study aimed to compare the diagnostic efficacies of 18F-FDG PET/CT and 68Ga-DOTANOC PET/CT in EAS. Methods The clinical and imaging data of 68 patients with EAS who underwent 18F-FDG PET/CT and 68Ga-DOTANOC PET/CT examinations from December 2016 to April 2021 were analyzed retrospectively, and the diagnostic efficacies of these methods were compared. Results In 37 cases, imaging was performed to locate the primary tumor lesion (localization group), and in 31 to evaluate tumor load or metastasis (staging group). Primary tumors were detected in 48.65% (18/37) of the localization group patients. According to scan-based analysis, the tumor lesion detection rates and false positive rates of 18F-FDG PET/CT imaging and 68Ga-DOTANOC PET/CT imaging were 18.92% vs. 45.95% (p < 0.05) and 21.62% vs. 2.70% (p < 0.05) respectively. For lesion-based analysis, the tumor lesion detection rates and false positive rates were 24.13% vs. 58.62% (p >0.05) and 31.04% vs. 3.45% (p < 0.05). In 90.32% (28/31) of the staging group patients, 286 of 292 lesions were confirmed as tumor lesions. Based on scan analysis, the detection rates and false positive rates of 18F-FDG PET/CT imaging and 68Ga-DOTANOC PET/CT imaging were 83.87% vs. 67.74% (p > 0.05) and 12.90% vs. 9.68% (p > 0.05) respectively. Based on lesion analysis, the detection rate and false positive rates were 93.84% vs. 54.80% (p < 0.05) and 1.37% vs. 1.03%(p > 0.05). Conclusion 68Ga-DOTANOC PET/CT imaging may be more suitable than 18F-FDG PET/CT for identifying the primary tumor in patients with EAS, while 18F-FDG PET/CT may be more advantageous than 68Ga-DOTANOC PET/CT for patients with suspected metastasis.